Shari’ah risk management framework for Islamic financial institutions - Hassan, Rusni (ISTAC, 2015)
In addition to systematic and unsystematic risks faced by traditional financial institutions, Islamic banks are widely exposed to Shari’ah risks with regards to the needs for ensuring Shari’ah compliance of its operational activities and financial products. In order to mitigate these additional risks, IFIs are urged to establish a comprehensive Shari’ah risks management tool that can help them to monitor their banking, financing and investment activities in conformity with Shari’ah principles and hence enhance their sustainability in the long run. Therefore, the objective of this paper is to contribute to the discussion on the development of the Shari’ah risk management framework for IFIs. This paper refers to Islamic primary sources of knowledge, the Quran and hadith in scrutinizing the permissibility of risk management practices by IFIs. The processes that take place in Shari’ah risk management; (i) risk identification; (ii) risk measurement and; (iii) risk monitoring/controlling are then thoroughly discussed. This paper hopes to shed some light on the importance of having a comprehensive standard of procedures in performing Shari’ah risk management function.